Awareness: Treatment and Prevention of Anemia among Higher Primary School Girls - Belagavi, Dayanand; John, Manju (International Journal of Psychosocial Rehabilitation, 2020)
Introduction: Among school-aged children, anemia is considerably known to be a global public health problem. Awareness about anemia in this age group enhances children’s learning potential in schools and increases their fitness and work capacity. Objective: To assess the knowledge regarding treatment and prevention of anemia among higher primary school girls between urban and rural schools. Methodology: A descriptive comparative study was conducted among 450 (urban) and 450 (rural) schoolgirls at higher primary schools in the Belgaum district, Karnataka. The stratified random sampling technique was used to select the schoolgirl children. A closed-ended structured knowledge questionnaire was designed to assess the knowledge. Results: The majority of 410 (91.1%) participants had poor knowledge, 36 (8.0%) had average knowledge, and only 4 (0.9%) had good knowledge in urban areas, whereas in rural higher primary schools, 348 (77.3%), 100 (22.2%), and 2 (0.4%) had poor, average, and good knowledge, respectively. The mean knowledge score was 8.46 in urban areas, higher as compared to the mean knowledge score of 6.54 in rural higher primary school girl children. Further, the knowledge score of urban school children was associated with their age, class, mother’s education, and family income (p-value < 0.05). Moreover, in rural schools, no significant association was found between knowledge scores and type of diet, mothers’ occupation, religion, type of family, or number of siblings of participants (p value > 0.05). Conclusion: The current study showed the majority of schoolgirls had poor knowledge regarding anemia in both urban and rural areas. Educational intervention with creative innovations for awareness regarding prevention of anemia is required to overcome this issue.